Sinergitas TNI dalam Penanggulangan Bencana Nasional - Betharia Pardosi; Novky Asmoro; Muliahadi Tumanggor (UNIB Press, 2026)
Indonesia's high exposure to disaster risk requires governance that is rapid, coordinated, and capable of integrating civilian and military resources. This article aims to analyze the role of the Indonesian National Armed Forces (TNI) in disaster management under Military Operations Other Than War (MOOTW) and to explain civil-military synergy that supports national crisis management. The study uses a descriptive qualitative approach based on a literature review. The analysis combines organizational sociology and crisis management perspectives to examine the disaster-management cycle, civil-military coordination, command adaptation, integrated command structures, and institutional learning. The findings show that TNI's main strengths are most visible during emergency response through command discipline, logistics, mobility, medical support, access opening, and rapid deployment of resources to affected areas. However, the effectiveness of TNI involvement depends on a clear division of roles, integrated command posts, shared operational information, interoperability, and sustained coordination across pre-disaster, emergency, and post-disaster phases. The article concludes that TNI involvement should remain complementary, proportional, time-bound, adaptive, and under civilian authority so that military capabilities strengthen rather than replace civilian disaster-management institutions while supporting sustainable national resilience.